2018
DOI: 10.1158/1078-0432.ccr-17-3725
|View full text |Cite
|
Sign up to set email alerts
|

The IGF2/IR/IGF1R Pathway in Tumor Cells and Myofibroblasts Mediates Resistance to EGFR Inhibition in Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a desmoplastic tumor of the biliary tree in which epidermal growth factor receptor (EGFR) is overexpressed and contributes to cancer progression. Although EGFR has been envisaged as a target for therapy, treatment with tyrosine kinase inhibitors (TKI) such as erlotinib did not provide therapeutic benefit in patients with CCA, emphasizing the need to investigate resistance mechanisms against EGFR inhibition. Resistant CCA cells to EGFR inhibition were obtained upon long-time exposure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 51 publications
4
76
0
Order By: Relevance
“…CSCs, a small part of cells, are present in heterogeneous tumors, and play a critical role in the initiation and progression of cancer and exhibition of strong chemoresistance to conventional chemotherapeutic drug treatment. 31 35 For these reasons, understanding the mechanism by which cancer cells enhance stemness may further facilitate cancer therapies. Yadav et al investigated germ line variants in CSC gene variants, and confirmed the essential role of CSCs in GBC susceptibility, prognosis and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…CSCs, a small part of cells, are present in heterogeneous tumors, and play a critical role in the initiation and progression of cancer and exhibition of strong chemoresistance to conventional chemotherapeutic drug treatment. 31 35 For these reasons, understanding the mechanism by which cancer cells enhance stemness may further facilitate cancer therapies. Yadav et al investigated germ line variants in CSC gene variants, and confirmed the essential role of CSCs in GBC susceptibility, prognosis and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Results were analyzed using Kaluza analysis software (Beckman-Coulter). Immunofluorescence assays were performed as previously described [44]. Primary antibodies are provided in Table 1.…”
Section: Iv8 Rons Determination In Culture Mediamentioning
confidence: 99%
“…Tyrosine kinase inhibitors, such as erlotinib, inhibit EGFR activation and have anti-cancer effects, although CCA tumors often have resistance to EGFR inhibitors [62]. Vaquero et al generated erlotinib-resistant CCA cells by escalating exposure to erlotinib from 1 to 20 µM and found that resistant CCA lines, including Mz-ChA-1, HuCCT1, and SK-ChA-1 cells, expressed higher levels of IGF-2 and IGF-1R as well as insulin receptor (IR) [63]. IR/IGF-1R inhibitor, linsitinib, decreased tumor volumes in xenograft mice with erlotinib-resistant CCA tumors [63].…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…Vaquero et al generated erlotinib-resistant CCA cells by escalating exposure to erlotinib from 1 to 20 µM and found that resistant CCA lines, including Mz-ChA-1, HuCCT1, and SK-ChA-1 cells, expressed higher levels of IGF-2 and IGF-1R as well as insulin receptor (IR) [63]. IR/IGF-1R inhibitor, linsitinib, decreased tumor volumes in xenograft mice with erlotinib-resistant CCA tumors [63]. A study analyzing serum and bile samples of 29 patients with extrahepatic CCA, 19 patients with pancreatic cancer, and 25 patients with benign biliary abnormalities found that CCA patients have significantly elevated levels of IGF-1 in bile compared to other patient groups but not in serum [64].…”
Section: Insulin-like Growth Factormentioning
confidence: 99%